PALINOLOGIA ESTRATIGRAFICA DEL JURASICO DE LA SIERRA DE CHACAI CO Y ADYACENCIAS (CUENCA NEUQUINA, REPUBLICA ARGENTINA). III: DESCRIPCIONES SISTEMATICAS DE LOS PALINOMORFOS DE LA FORMACION CURA NIYEU (BAYOCIANO) (Ameghiniana, 2013)
ABSTRACT: STRATlGRAPHlC PALINOLOGY OF THE JURASSIC OF SIERRA DE CHACAICó AND NEIGHBOURING AREAS (NEUQUÉN BASIN, ARGENTINA). III: SYSTEMATlC DESCRIPTlON OF PALYNOMORPHS OF THE CURA NIYEU FM. (BAJOCIAN). - 78 terrestrial and marine species of palynomorphs, belonging to 5 microfloristic assemblages of the Cura Niyeu Fm. at the type locality, have been identified. The species belong to the following genera: